Teori Progresif Jhon Dewey Relevansinya terhadap Pendidikan Moral P5 di SMP Muhammadiyah 7 Surakarta - Pakpahan, Akbar Waliyuddin; Anugrah, Abror Dikna; Faizal, Ihsan; Fauzi, Ahmad; Ali, Mohamad (TSAQOFAH, 2025)
This study aims to analyze the application of the learning by doing principle in Moral Education based on the Pancasila Student Profile (P5) at SMP Muhammadiyah 7 Surakarta and to identify factors influencing its success or challenges in implementation. A descriptive qualitative approach was employed, involving students, teachers, and parents as research subjects. Data collection techniques included in-depth interviews, participatory observation, and document analysis. Data were thematically analyzed to identify key themes related to strengthening students' moral values through experiential learning activities. The findings reveal that the learning by doing principle in P5 is implemented through activities integrating Islamic values and real-life practices, such as social actions and environment-based learning. However, several challenges were identified, including time constraints, students' limited understanding of moral concepts, and a lack of parental involvement. The study concludes that the learning by doing principle holds significant potential in enhancing students' moral values but requires stronger collaboration between teachers, students, and parents to ensure more effective implementation. These findings contribute to the development of experiential-based moral education in Islamic school settings.